Forensic Monitoring Project Report: Raštani and Vojno Exhumations State Commission on Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather From 21-22 May 1998 the State Commission on Missing Persons (Bosniak) exhumed the remains of four individuals from seven sites north of Mostar in the vicinity of Raštani. At the time of the reconnaissance visits these sites were collectively expected to contain the graves of approximately 100 prisoners killed by an HVO military unit. These prisoners were alleged to have been initially taken by Bosnian Serbs and then handed over to Bosnian Croats in 1993 and early 1994. Place of Exhumation: Raštani, Vojno Exhumation Site: Raštani 1, Raštani 2, Vojno Polje, Raštani Railroad Track 1 & 2, Vojno 0, Vojno 1 Date of Exhumation: 21-22 May 1998 Minimum Number of Exhumed Individuals: 004